ADAPTIVE OPTICS IMAGING OF FOVEAL SPARING IN GEOGRAPHIC ATROPHY SECONDARY TO AGE-RELATED MACULAR DEGENERATION. Issue 2 (February 2016) - Querques, Giuseppe; Kamami-Levy, Cynthia; Georges, Anouk; Pedinielli, Alexandre; Capuano, Vittorio; Blanco-Garavito, Rocio; Poulon, Fanny; Souied, Eric H.
Abstract : Background: To describe adaptive optics (AO) imaging of foveal sparing in geographic atrophy (GA) secondary to age-related macular degeneration. Methods: Flood-illumination AO infrared (IR) fundus images were obtained in four consecutive patients with GA using an AO retinal camera (rtx1; Imagine Eyes). Adaptive optics IR images were overlaid with confocal scanning laser ophthalmoscope near-IR autofluorescence images to allow direct correlation of en face AO features with areas of foveal sparing. Adaptive optics appearance of GA and foveal sparing, preservation of functional photoreceptors, and cone densities in areas of foveal sparing were investigated. Results: In 5 eyes of 4 patients (all female; mean age 74.2 ± 11.9 years), a total of 5 images, sized 4° × 4°, of foveal sparing visualized on confocal scanning laser ophthalmoscope near-IR autofluorescence were investigated by AO imaging. En face AO images revealed GA as regions of inhomogeneous hyperreflectivity with irregularly dispersed hyporeflective clumps. By direct comparison with adjacent regions of GA, foveal sparing appeared as well-demarcated areas of reduced reflectivity with less hyporeflective clumps (mean 14.2 vs. 3.2; P = 0.03). Of note, in these areas, en face AO IR images revealed cone photoreceptors as hyperreflective dots over the background reflectivity (mean cone density 3, 271 ± 1, 109 cones per square millimeter). Microperimetry demonstrated residual function in areas of foveal sparing detected by confocal scanning laser ophthalmoscope near-IR autofluorescence. Conclusion: Adaptive optics allows the appreciation of differences in reflectivity between regions of GA and foveal sparing. Preservation of functional cone photoreceptors was demonstrated on en face AO IR images in areas of foveal sparing detected by confocal scanning laser ophthalmoscope near-IR autofluorescence. Abstract : In this study, the authors demonstrated that adaptive optics (AO) allows the appreciation of differences in reflectivity between regions of geographic atrophy and foveal sparing.